Quantitative non-nutritive sucking measurement as a predictor of oral feeding readiness in newborns - Lee, Kyeong Jae; Shin, Yong Beom; Park, Ho Eun; Choi, Suro; de Oliveira, Jean G.; Hong, Daun; Kim, Sohee; Yoon, Jin A (Frontiers in Pediatrics, 2023)
Background and purpose: The purpose of this study is to examine the relationship between the parameters of a silver nanowire-based flexible pressure sensor developed to measure the non-nutritive sucking (NNS) performance and predict the nutritive sucking status in preterm infants. Methods: Preterm infants who were referred for feeding difficulty during the transition period from tubal feeding to oral feeding were enrolled in our study. A flexible pressure sensor was used to measure the non-nutritive sucking parameters of neonates. The evaluator stimulated the infants' lips and tongue with a pacifier with a sucking pressure sensor inserted to check whether non-nutritive sucking had occurred. When the sucking reflex was induced, it was measured. The infants’ sucking characteristics were subdivided into classifications according to the NOMAS criteria and full oral feeding (FOF) status. Quantitative NNS measurement according to the feeding state was compared between groups. Results: When comparing the quantitative NNS measurement by feeding characteristics, the average sucking pressure was significantly higher in infants in the FOF capable group than those in the incomplete FOF group. In addition, the maximum and average sucking pressure was significantly higher in infants with a normal sucking pattern compared to those with a disorganized sucking pattern. The average NNS pressure was divided over the range of 0 to 3 and the same weight was assigned to each item. When the optimal cut-off value for the sensitivity and specificity of the average NNS pressure to estimate the FOF was set, a pressure of 1.5 kPa yielded the highest sensitivity (84.62%) and specificity (67.65%) on the Receiver operating characteristic (ROC) curve. The Area under the curve (AUC) was 0.786, and this result was statistically significant. Conclusions: This study presents a quantitative parameter for non-nutritive sucking in preterm infants with the use of a flexible pressure sensor. Results show possible quantitative indicators that can aid in predicting when preterm infants can transition to oral feeding and their prognosis. This will serve as a basis for future research on determining the feeding transition period of newborns with health conditions that affect oral feeding.